Resource reuse of American cockroach (Periplaneta americana) residue fermented by Bacillus subtilis in the feed for juvenile largemouth bass (Micropterus salmoides) - Li Chen; Qiujie Chen; Xiaofang Zou; Xin Li; Xiaowen Long (Aquaculture Reports)
A 9-week feeding experiment was conducted to investigate the effects of substituting dietary fish meal with fermented American cockroach residue (FACR) on the growth, metabolism, antioxidant capacity, immunity, and intestinal health of juvenile largemouth bass. Five diets were prepared, where FACR replaced fish meal at 0 %, 15 %, 30 %, 45 %, and 60 % levels, and were fed to juvenile largemouth bass. The results showed that fish in the 0 %, 15 %, and 30 % replacement groups had higher final body weight, weight gain rate, and specific growth rate than those in the 45 % and 60 % groups. The 45 % replacement group had the highest whole-body crude protein content, and the crude lipid content peaked at 30 % replacement. Trypsin activity in the liver and stomach decreased significantly in the 45 % and 60 % groups, whereas the intestinal α-amylase activity exhibited a significant reduction in the 60 % group. Serum total protein was highest in the 45 % replacement group, and serum aminotransferase activities were lower in the 15 %, 30 %, 45 %, and 60 % groups compared to the control. The 30 % group had the lowest serum urea nitrogen content. Liver and serum triglyceride and total cholesterol levels decreased with increasing FACR, while liver glucose increased. Immunological indicators were enhanced at 15 % and 30 % replacement but decreased at higher levels. Histological analysis showed that the 15 % group had thicker muscle, the 30 % group had the widest villi, and the control group had the greatest crypt depth. Intestinal microbiota analysis indicated a reduction in richness and diversity with increasing FACR. PCA showed different microbial compositions between FACR and control groups. In summary, replacing 15 % of dietary fish meal with FACR did not harm growth performance but improved body crude protein content, digestive enzyme activity, antioxidant capacity, immunity, and intestinal microbiota composition, promoting the overall health and growth of juvenile largemouth bass.